2014
DOI: 10.3892/mmr.2014.2670
|View full text |Cite
|
Sign up to set email alerts
|

Screening for serum biomarkers in patients with chronic hepatitis B with hepatitis B surface antigen seroclearance, following pegylated interferon alpha therapy

Abstract: Chronic hepatitis B (CHB) is one of the most common infectious disease worldwide and a leading cause of death. Hepatitis B surface antigen (HBsAg) has previously been proven to be a steady biomarker that may be used to predict clinical outcomes. The amount of circulating HBsAg has been reported to reflect the number of infected hepatocytes. An advantage of pegylated interferon alpha (peg-IFN-α) is that as a finite course of therapy, it can potentially lead to sustained disease remission in subsequent decades. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Recently, in studies on new treatments that include a combination of nucleotide drugs and IFNs, we showed that patients with HBeAg‐positive CHB and a partial viral response to NUC therapy can achieve undetectable HBsAg and HBeAg seroconversion after switching to PegIFN‐2α treatment . Genetic variation in STAT and IFNC1can predict the response to IFN‐α therapy. It was reported that STAT4 rs7574865 is a reliable predictor of the response to IFN‐α therapy .…”
Section: Cytokines and Hbsag Seroclearancementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in studies on new treatments that include a combination of nucleotide drugs and IFNs, we showed that patients with HBeAg‐positive CHB and a partial viral response to NUC therapy can achieve undetectable HBsAg and HBeAg seroconversion after switching to PegIFN‐2α treatment . Genetic variation in STAT and IFNC1can predict the response to IFN‐α therapy. It was reported that STAT4 rs7574865 is a reliable predictor of the response to IFN‐α therapy .…”
Section: Cytokines and Hbsag Seroclearancementioning
confidence: 99%
“…A number of studies have indicated that using a fixed course of polyethylene glycol-modified IFN can improve the immune function, the sustained response rate (HBeAg seroconversion in some patients appears even as HBsAg seroconversion) and the long-term prognosis of patients with CHB. [67][68][69] A recent study has described a new type of IFN, namely, PegIFN-lambda-1a (Lambda), a type III IFN that has antiviral activity against HBV and hepatitis C virus in vitro. Treatment with Lambda has been shown to exert stronger early effects on HBV-DNA and quantitative HBsAg.…”
Section: Interferonsmentioning
confidence: 99%
See 1 more Smart Citation